Pemanfaatan Sistem Informasi Geografis untuk Analisa Potensi Sumber Daya Lahan Pertanian di Kabupaten Kudus - Gunawan, Budi (Universitas Muria Kudus, 2011)
Kudus is an agricultural and industrial city. To find out how the use of land in Kudus especially farmland needed an information system that will support it. One technology that facilitate this is to use Geographic Information System (GIS). GIS is a computer-based information sistim and digital data so that the management and its presentation is better than to manual. GIS data obtained from satellite images to map the earth with digital data that can be used for GIS in accordance with the needs, in other words the availability of digital data can be from a few years back until the current data. This study tries to map the potential of land, especially farmland in Kudus with this Geographic Information System.